Elite volleyball coaches' experience using a statistical information system - Gesbert, V.; Carrel, J.; Philippe, R. A.; Hauw, D. (International Journal of Performance Analysis in Sport, 2016)
This study investigated how elite volleyball coaches enhance team management by using statistical tools that describe players' behaviours. The focus was particularly on tool usability via a user-experience approach. Five elite male coaches volunteered to participate. Verbalisation data were collected during semi-structured interviews and examined by inductive content analysis (Biddle et al., 2001). The results showed that usability was linked to 15 raw themes (e.g. taking into account the value of the opponent) grouped into six first-order themes (e.g. to balance the statistical data) and then two high-order categories of experience (i.e. knowledge of the situated properties of the statistical tool and know-how for using the statistical tool). These results revealed that the coaches used the statistical tools in a situated, selective and parsimonious way and that their humanistic side was unaffected by the tool. Our findings emphasise that statistical tool use is not an addition to coaching activity but instead indicates a reorganisation in the activity. The key perspectives of this study are twofold: (a) the information focused on user experience should be included at the beginning of the design process to make statistical tools more relevant; (b) the list of knowledge and knowhow linked to the use of statistical tool may be included in guidelines for training program for coaching education.